The Effectiveness of Chatgpt in Completing Astronomy Lectures: Building Awareness of Its Use - Hikmatiar, Hamzarudin; Sya’bania, Nursina; Jayadin, Jayadin; Kasman, Risqah Amaliah; Imranah, Imranah; Sahlan, Sahlan; Saputra, Sabarudin (Universitas Muhammadiyah Makassar, 2024)
The use of ChatGPT provides new opportunities for students to deepen their understanding of the course materials and overcome the obstacles they may encounter. The study of astronomy itself includes material that studies the universe, but students tend to minimize the related knowledge. The emergence of open AI products is considered a good solution to address the acceleration of specialized student learning in tasks. This research aims to find out whether ChatGPT has benefits for students in completing astronomy lecture assignments at the Muhammadiyah University of Maumere. This is seen from how often students use ChatGPT. The research method used is a mixed method that combines quantitative and qualitative analysis. Quantitative data is obtained from questionnaires which are presented in the form of numerical data, while qualitative data is additional information obtained through conversations between researchers and research sources. Data collection is carried out using an app that is shared with students through Google Forms after ChatGPT is applied to complete college tasks. This type of activity is considered to have excellent benefits for the completion of tasks in education. Based on the research results, it was found that 13 or 65% of the total respondents stated that ChatGPT was very good to use in completing tasks. Apart from that, using ChatGPT was also considered effective in completing astronomy lecture assignments because 50% of students stated that using ChatGPT was very effective in solving astronomy problems, while the other 50% chose only effective. Based on these findings, it is fundamental that ChatGPT has benefits for students to help solve lecture problems and can be a recommendation for other users provided they always pay attention to the ethics of its use.